FRI0551 PERFORMANCE OF THE 2019 AMERICAN COLLEGE OF RHEUMATOLOGY/EUROPEAN LEAGUE AGAINST RHEUMATISM SYSTEMIC LUPUS ERYTHEMATOSUS CLASSIFICATION CRITERIA. (13th June 2020) - Vrancianu, C.; Conea, I.; Boca, A.; Bolboceanu, M.; Draganesscu, C.; Sasu, M.; Ciofu, C.; Macovei, L.; Milicescu, M.; Bojinca, M.; Ancuta, I.; Mihai, C.; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) is a heterogenous autoimmune disease, with increased morbidity and mortality, often diagnosed in advanced stages. The recently published 2019 American College Of Rheumatology/European League Against Rheumatism (ACR/EULAR) classification criteria for SLE are weighted, hierarchically clustered criteria developed to increase reliability and the identification of early SLE. Objectives: To compare the sensitivity and specificity of the 2019 ACR/EULAR criteria with the 2012 SLICC criteria in a large single-centre cohort of patients with SLE, diagnosed according to expert oppinion. Methods: Data of SLE patients evaluated in our centre between 1996-2019 have been retrospectively analyzed. The control cohort included patients with positive antinuclear antibodies of other ethiology than SLE, evaluated between 2001-2019. The sensitivity and specificity of the 2019 ACR/EULAR and 2012 SLICC criteria were tested using the McNemar test for correlated proportions. Results: Four hundred and forty-six patients with SLE (413 women, mean±SD age 40.5±12.7 years, disease duration 10.1±9.2 years) and 67 controls (63 women, mean±SD age 50.4±12.6 years, disease duration 7.6±6.9 years; 29 systemic sclerosis (SSc), 18 mixed connective tissue dissease (MCTD), 15 undifferentiated CTD, 2 rheumatoid arthritis (RA), 2 SSc – RA overlaps and 1 dermatomyositis) were included. The sensitivity of the 2019 ACR/EULAR and 2012 SLICC criteria were similar 85.4% and 83.6 %, respectively (p=0.3). The specificity of the 2019 ACR/EULAR and 2012 SLICC criteria were 70.2 % and 86.6%, respectively (p=0.007). In the SLE group, patients missclassified according to the new 2019 ACR/EULAR criteria were 65, whereas according to the 2012 SLICC criteria were 73; of them, 44 patients did not fulfill any criteria. In the control group, patients misclassified had mainly MCTD (13/20 patients according to the new 2019 ACR/EULAR, and 8/9 according to the 2012 SLICC criteria). Conclusion: In this real-life cohort, the 2019 ACR/EULAR criteria have a similar sensitivity and lower specificity than the 2012 SLICC criteria, misclassifying especially MCTD patients. These results might be due to the long disease duration in our cohort. References: [1] Aringer M, Costenbader K, Daikh D, et al. 2019 European League Against Rheumatism/American College of Rheumatology Classification Criteria for Systemic Lupus Erythematosus. Arthritis Rheumatol. 2019;71(9):1400–1412. doi:10.1002/art.40930 Disclosure of Interests: None declared